2020
DOI: 10.12681/psy_hps.23273
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastination in Greek Higher Education: Shedding Light on a Darkened yet Critical Issue

Abstract: Αcademic procrastination, characterized by self-regulation difficulties in delaying the start or completion of academic tasks (Ferrari, 2010), is widespread among university students. One of the most widely used measures of academic procrastination is Procrastination Assessment Scale Students (PASS, Solomon &Rotblum, 1984). However, there is adearth of research investigating its factorial structure using confirmatory factor analysis. Greek studies on academic procrastination are also scarce. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…It is reported that over 70% of college students regularly postpone educational tasks such as readings and writing assignments [ 7 , 8 ]. Moreover, over 40% of college students have self-identified as frequent procrastinators [ 9 ]. Extensive studies have explored the consequences caused by AP.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that over 70% of college students regularly postpone educational tasks such as readings and writing assignments [ 7 , 8 ]. Moreover, over 40% of college students have self-identified as frequent procrastinators [ 9 ]. Extensive studies have explored the consequences caused by AP.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Kármen et al, (2015) that based on recent studies, 70% of university students thought that procrastination in the academic situation is a very common phenomenon and believes that procrastination as characteristic of their academic activities. Argiropoulou and Ferrari (2014) also affirm that over 75% of university students procrastinate frequently, particularly towards meeting study obligations, and it was reported that the students delay their tasks due to academic difficulties. Moreover, Solomon and Rothblum (1994) assert that university students tend to procrastinate to a great extent, especially when it comes to tasks most closely related to their academic performance.…”
Section: Findings and Discussionmentioning
confidence: 65%
“…30% of participants reporting to procrastinate on reading weekly assignments and 20% reporting to procrastinate on writing a term paper. Besides, Argiropoulou and Ferrari (2014) also found that reading weekly assignments with 23.5% of the participant were procrastinate on this task. 19.2% of the participants reported procrastinate on writing a term paper, 14.3% procrastinate on course attendace.…”
Section: Findings and Discussionmentioning
confidence: 75%
“…Hoci odhady jej miery nie sú jednotné, udáva sa, že 30-60 % študentov odkladá plnenie školských úloh (Rabin et al, 2011). V niekoľkých výskumoch sa preukázala vyššia miera akademickej prokrastinácie u mužov (Balkis, & Duru, 2017;Steel, 2007;Ozer, & Ferrari, 2011), avšak prítomnosť rodových rozdielov nebola v ďalších výskumoch jednoznačne potvrdená (Argiropoulou et al, 2016;Schweigerová, & Slavkovská, 2015). Slabá pozitívna korelácia bola zistená medzi akademickou prokrastináciou a prežívanou úzkosťou i depresívnym prežívaním (Eisenbeck et al, 2019;Senécal et al, 1995).…”
Section: Základné Súvislosti Nerozhodnosti úZkosti a Akademickej Prokrastinácieunclassified